2021
DOI: 10.3390/jcm10163637
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Adipose-Derived Stem Cells (ADSCs) and Stromal Vascular Fraction (SVF) in Skin Scar Treatment—A Systematic Review of Clinical Studies

Abstract: In recent years, lipofilling became a popular scar treatment method. Its beneficial outcomes have been partly attributed to the regenerative capacity of adipose-derived stem cells (ADSCs), suspended in an extracellular matrix—the stromal vascular fraction (SVF). The aim of this review was to verify if existing data support the clinical use of ADSC-related interventions in scar treatment. A systematic search of the literature was performed in July 2020 in five databases (Medline, Cochrane, Web of Science, Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…A systematic review of 665 patients also showed the beneficial effects of SVF-related interventions in the treatment of scarring. Some studies show that SVF injection interventions can be moderately effective in scar healing and are not inferior to PRP or fractional CO2 laser [43]. Past studies have shown that acne can lead to create a variety of prominent and erythematosus scars and influence patients' lives, so it is important to identify new therapeutic strategies [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 665 patients also showed the beneficial effects of SVF-related interventions in the treatment of scarring. Some studies show that SVF injection interventions can be moderately effective in scar healing and are not inferior to PRP or fractional CO2 laser [43]. Past studies have shown that acne can lead to create a variety of prominent and erythematosus scars and influence patients' lives, so it is important to identify new therapeutic strategies [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…ADSCs and SVFs obtained from the mechanical centrifugation displayed a significantly higher concentration of mature pericytes, ADSCs, and exosomes, when compared to isolated cells with enzymatic digestion [ 52 ]. During the last few years, ADSC and SVFs-based cellular therapies have been tested in several clinical settings, like wound healing [ 51 , 53 , 54 ], hair regrowth [ 55 ], and breast augmentation [ 56 ]. Some studies have highlighted several common points between the biomolecular pathway of ADSCs in wound healing and hair regrowth, particularly the Wnt signaling pathway [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, ADSCs even was used as a new regenerative immediate therapy in COVID-19 patient’s treatment thanks to their immunomodulatory and anti-inflammatory activities promoting the wound healing in damaged tissue by a cytokine storm [ 58 , 59 ]. For soft tissue defects and chronic wounds, ADSCs have been employed in conjunction with a fat grafting technique or with dermal substitute scaffolds and PRP [ 54 , 60 ]. In recent years, EVs have been considered a new perspective in the therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…These extracellular vesicles have been found to release miR-21, miR-181b, matrix metalloproteinases, milk fat globule EGF (MFG-E8), angiopoietin-like 1, and miR-375 to promote the neoangiogenesis during soft tissue healing and induce osteoblast differentiation and bone regeneration [47][48][49]. This expanded knowledge strongly promoted the initial enthusiasm in ASCs-based therapy, and during the following years, several investigations studied their clinical applicability to treat, among the others, osteoarthritis [50], Parkinson's disease [51], stroke [52,53], diabetic kidney disease [54], spinal cord injury [55], cutaneous scars [56], chronic skin wounds and soft tissues defects [57], burn wounds [58], alveolar ridge regeneration [59], Chron's disease [60], liver regeneration after partial hepatectomy [61], Graft-versus-Host disease [62], facial nerve regeneration [63], and intervertebral disc degeneration [64]. Nevertheless, it should be underlined that most of the initial expectations regarding the osteogenic properties of ASCs have been downsized by the following researchers, who demonstrated their limited differentiation potential toward osteogenic lineage [65].…”
Section: Ascs Potentialmentioning
confidence: 99%